Discourse analysis - Brown, Gillian (Cambridge University Press, 1983)
The authors provide an extensive overview of the many and diverse approaches to the study of discourse, but base their own approach centrally on the discipline which, to varying degrees, is common to them all - linguistics. Using a methodology which has much in common with descriptive linguistics, they offer a lucid and wide-ranging account of how forms of language are used in communication. Their principal concern is to examine how any language produced by man, whether spoken or written, is used to communicate for a purpose in a context. The discussion is carefully illustrated throughout by a wide variety of discourse types